Peran Guru Dalam Pengembangan Karakter Peserta Didik Di Sekolah Menengah Pertama Negeri 1 Sawit Seberang, Langkat. - Isnaini, Putri (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study aims to reveal the role of teachers as example with in development of the character studets and the factors that influence development of character students of State Junior High School (SMPN) 1 Sawit Seberang, Langkat. This study used the descriptive qualitative approach. The subjects were the headmaster, headmaster deputies, teachers, studeats, and chairman of the committee of SMPN 1 Sawit Seberang, Langkat. Techniques used to collect data were interview, observation, and documentation. The data analysis used interactive model of Miles Huberman, following the steps of data reduction, data presentation, and conclusion drawings. The results of the research show the following the role of teachers as example must be demonstrated through speech, attitude, and personality, like courtesy, discipline, responsibility, tolerance, honesty, and concern for students and others. The factors that support development of character students include their commitment to the school community, the curriculum standard content, headmaster leadership, and togetherness. The factors that inhibit the development of character students include the limited financial resources, lack of awareness of parents, and in different attitude of some teachers and students.